Predisposing, enabling, and reinforcing factors for the success of antiretroviral (ARV) treatment among people living with HIV - Atmajaya, Yudhi; Wardani, Dyah Wulan Sumekar Rengganis; Susianti, Susianti (Holistik Jurnal Kesehatan, 2024)
Background: The Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) epidemic is now growing rapidly and becoming one of the biggest challenges, despite various efforts to control and suppress its transmission. Globally, HIV/AIDS is a health problem that can cause a multidimensional crisis. The HIV/AIDS control program is aimed at reducing morbidity and hospitalization rates, mortality due to AIDS, and improving the quality of life of HIV sufferers. Purpose: To determine the effect of predisposing, enabling, and reinforcing factors on the success of antiretroviral (ARV) treatment in people with HIV/AIDS. Method: A Quantitative research of cross-sectional analytical survey conducted at the Bandar Lampung City Health Center for 2 months in January-February 2024. The number of samples in this study was 122 respondents taken using purposive sampling technique. The instrument used was a questionnaire that had been declared valid in the validity and reliability tests. Data analysis used univariate and bivariate chi-square tests with confidence intervals (CI), significance level p <0.05. Results: Several factors that influence success include clinical stage (p-value=0.014), comorbidities (p-value=0.000), and treatment adherence (p-value=0.000). Conclusion: There is a significant influence between clinical stage, comorbidities, and adherence to the success of ARV treatment. Meanwhile, there is no significant relationship between the duration of ARV treatment and the combination of ARV therapy with the success of treatment. In increasing the success of treatment, people with HIV/AIDS must maintain their health so that opportunistic infections (HIV comorbidities) do not occur and remain in the early clinical stage.   Keywords: Antiretroviral (ARV); Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS); People Living with HIV (PLHIV); Threatment.   Pendahuluan: Epidemi Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) kini semakin berkembang cepat  dan menjadi salah satu tantangan terbesar, meskipun telah dilakukan berbagai upaya untuk mengendalikan serta menekan penularannya. Secara global HIV AIDS merupakan masalah kesehatan yang dapat menyebabkan krisis multidimensi. Program pengendalian HIV/AIDS ditujukan untuk menurunkan angka kesakitan dan rawat inap, angka kematian yang berhubungan dengan AIDS, dan meningkatkan kualitas hidup orang terinfeksi HIV. Tujuan: Untuk mengetahui pengaruh faktor predisposing enabling dan reinforcing terhadap keberhasilan pengobatan ARV pada ODHIV. Metode: Penelitian kuantitatif survei analitik cross sectional yang dilakukan di Puskesmas Kota Bandar Lampung selama 2 bulan pada bulan Januari-Februari 2024. Jumlah sampel pada penelitian ini sebanyak 122 responden yang diambil menggunakan teknik purposive sampling. Instrumen yang digunakan berupa kuesioner yang telah dinyatakan valid pada uji validitas dan reliabilitas. Analisis data yang digunakan univariat dan bivariat uji chi square dengan confidence interval (CI), tingkat kemaknaan p<0.05. Hasil: Beberapa faktor yang memengaruhi keberhasilan antara lain, stadium klinis (p-value=0.014), penyakit penyerta (p-value=0.000), dan kepatuhan pengobatan (p-value=0.000). Simpulan: Terdapat pengaruh yang bermakna antara stadium klinis, penyakit penyerta, dan kepatuhan terhadap keberhasilan pengobatan ARV. Meskipun tidak terdapat hubungan yang bermakna antara lama pengobatan dan paduan terapi ARV dengan keberhasilan pengobatan. Dalam meningkatkan keberhasilan pengobatan ODHIV harus menjaga kesehatan agar tidak terjadi infeksi oportunistik (penyakit penyerta HIV) dan tetap pada stadium klinis awal.   Kata Kunci: Antiretroviral (ARV); Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS); Pengobatan.